A preliminary study on intention to adopt IoT-enabled smart home systems in Shanzhen of China - Song, Yuchen; Bohari, Abdul Manaf; Thi, Lip Sam (International Journal of Innovative Research and Scientific Studies, 2025)
This study seeks to investigate the combined influence of perceived ease of use, perceived usefulness, and personal innovation attributes on customers' readiness to embrace IoT smart home systems in Shenzhen, offering a theoretical foundation for product optimization and market strategies. This study examines the factors affecting the intention to adopt smart home devices, grounded in the Technology Acceptance Model (TAM) and the Howard-Sheth Consumer Behavior Model. Eight study hypotheses (H1-H8) are formulated through the development of a theoretical model, concentrating on the influence of elements such as perceived ease of use, perceived usefulness, perceived price, and perceived interest on customer adoption intention and purchase intention. The research employed a questionnaire survey method to gather accurate data and performed empirical tests utilizing combination reliability, mean variance extraction, and correlation analysis. The findings demonstrate that perceived simplicity of use and perceived usefulness significantly enhance consumers' attitudes and adoption intentions, hence confirming the fundamental hypothesis of the Technology Acceptance Model (TAM). This study establishes a theoretical framework for enhancing product design, pricing tactics, and marketing plans for smart home companies, while broadening the application contexts of the Technology Acceptance Model in the smart home sector.